Evidence-based telehealth clinical pathway for pediatric tympanostomy tube otorrhea. (July 2020) - Shaffer, Amber D.; Dohar, Joseph E.
Abstract: Introduction: As healthcare moves away from volume-based to value-based delivery models, evidence based clinical pathways detail essential steps in patient care to reduce the costs and utilization of health care resources. Ideal pathways lead towards standardized, patient-centered care through an algorithm that is evidence-based, interventions with criteria-based progression, and measurable endpoints or quality indicators. Using these standards, a clinical pathway for managing tympanostomy tube otorrhea beginning with phone triage was developed in accordance with AAO-HNSF Guidelines. Methods: A retrospective case series of all consecutive patients calling the otolaryngology nurse's line at a tertiary pediatric hospital 3/2018-11/2018 regarding otorrhea was performed. Nurses completed a standardized and evidence-based form based on parent responses regarding purulence, tympanostomy tubes/perforation, fever>102°, ear redness, bacterial rhinosinusitis, sore throat, and immunodeficiency, which was sent to the advanced practice providers (APPs) to assess for antibiotic drops. Otorrhea form information and tympanostomy tube history, subsequent phone calls, clinic visits, and antibiotic prescriptions for otorrhea were extracted. Results: Eighty-two patients were included. Median child age at phone call was 2.5 years (range 0.3–20.2 years), and 45.1% were female. All patients had prior tubes and active purulent otorrhea. No parents reported cellulitis or immunodeficiency. One patient had symptoms of bacterial rhinosinusitis and a sore throat but had already been seen by their primary care provider (PCP) for systemic antibiotics. Antibiotic drops were prescribed by an APP in 96.3% of cases [ofloxacin (n = 57), ciprofloxacin (n = 17), or ciprofloxacin with dexamethasone (n = 5)]. The remaining patients already had drops (2.5%) or were referred to their PCP (1.2%). Twenty (24.4%) received another antibiotic prescription and 17.1% had a subsequent clinic or urgent care visit for otorrhea. Conclusions: This pathway obviated clinic visits in 82.9% of patients with a 75.6% treatment cure. Highlights: First telehealth clinical pathway for pediatric acute tympanostomy tube otorrhea. 83% were diagnosed and treated without emergency room or office assessment. No adverse outcomes were noted. Future studies needed to refine indicators predicting failure.